1993
DOI: 10.2307/1602405
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transracial Adoption

Abstract: In the United States, the first transracial adoption placements in substantial numbers were of Japanese and Chinese children following World War II. During the 1950s, after the Korean War, Korean children were adopted by American families in large numbers. In the late 1960s and early 1970s, more than 10,000 African-American children were adopted by white parents. Subsequently, however, this practice decreased dramatically in response to strong condemnation by many African-American social workers and others.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 13 publications
0
35
0
6
Order By: Relevance
“…Thus, largely dealing with our known explicit formal transfers, we may find a plethora of academic approaches tackling with many different dimensions of such phenomenon, sometimes closely connected with further or parallel developments. For example the perception and conformation of identity(ies) among adoptees (Noy-Sharav, 2005) has led to explore the role of the racial and ethnic identity concerning the relationships between adoptive parents and their non-biological offspring, especially in transracial adoption (Dorow, 2006;Grice, 2005;Briggs, 2003;Westhues & Cohen, 1998;Silverman, 1993). Moreover, such studies have launched the interest on the perception and experiences of ethnic, national and familiar identities in different -though complementarycontexts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, largely dealing with our known explicit formal transfers, we may find a plethora of academic approaches tackling with many different dimensions of such phenomenon, sometimes closely connected with further or parallel developments. For example the perception and conformation of identity(ies) among adoptees (Noy-Sharav, 2005) has led to explore the role of the racial and ethnic identity concerning the relationships between adoptive parents and their non-biological offspring, especially in transracial adoption (Dorow, 2006;Grice, 2005;Briggs, 2003;Westhues & Cohen, 1998;Silverman, 1993). Moreover, such studies have launched the interest on the perception and experiences of ethnic, national and familiar identities in different -though complementarycontexts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many researchers have raised questions about the implications of adoption on adolescent development. For the most part, empirical research conducted in this area has reported positive outcomes (or similar outcomes as non-adopted counterparts) for adopted individuals (Brodzinksy, Smith, & Brodzinsky, 1998;Finley, 1999;McRoy & Zurcher, 1983;Silverman, 1993;Simon & Alstein, 1992), particularly compared to forms of institutional care (Feigelman and Silverman, 1984;Schorr, 2000;Burrow and Finley, 2001). …”
Section: Adoptionmentioning
confidence: 99%
“…Insofar as same race adoptions have been used in comparison with transracial adoptions, empirical research has generally indicated that these two groups do not significantly differ with regards to adjustment issues (McRoy & Zurcher, 1983;Triseliotis, Shireman, & Hundleby, 1997;Silverman, 1993;Simon & Alstein, 1992). Despite these findings, however, significant criticism remains within the literature regarding the purported inability of parents of one race to facilitate positive developmental outcomes for their adopted children of a different race.…”
Section: Transracial Adoptionmentioning
confidence: 99%
See 2 more Smart Citations